Former Yugoslav Republic of Macedonia : First Review Under the Precautionary Credit Line. (IMF Staff Country Reports; Country Report, 2011)
The report says that Macedonia continues to pursue sound economic policies that are consistent with the program supported by the Precautionary Credit Line (PCL) arrangement. The authorities strengthened debt management policies and improved access to external funding and developed a domestic public debt market. This will help Macedonia to meet its financing needs from private market sources in future. The PCL plays a valuable role in supporting market confidence by signaling Macedonia's commitment to prudent policies and strengthening its reserve buffers.